The Effects of Sentiment on Market Return and Volatility and The Cross-Sectional Risk Premium of Sentiment-affected Volatility - Yan Yang; Laurence Copeland (Cardiff University, Cardiff Business School, 2014)
We construct investor sentiment of UK stock market using the procedure of principal component analysis. Using sentiment-augmented EGARCH component model, we analyse the impacts of sentiment on market excess return, the permanent component of market volatility and the transitory component of market volatility. Bullish sentiment leads to higher market excess return while bearish sentiment leads to lower excess return. Sentiment-augmented EGARCH component model compares favourably to the original EGARCH component model which does not take investor sentiment into account. Furthermore, we test the cross-sectional risk premia of the permanent and transitory components of sentiment-affected volatility in the framework of ICAPM.
Keywords: G12; G15; 330; investor sentiment; principal component analysis; EGARCH component model; ICAPM; cross-sectional risk premium